Programmable droplet actuating platform using liquid dielectrophoresis. (20th April 2021) - Frozanpoor, Iman; Cooke, Michael; Racz, Zoltan; Bossons, Ian; Ambukan, Vibin; Wood, David; Gallant, Andrew; Balocco, Claudio
Abstract: Droplet motion has been a long-standing interest in microfluidics as it is often limited by the high operating voltages, which hampers the development of consumer applications. Forces generated by liquid dielectrophoresis (L-DEP) can enhance surface wetting, without requiring chemical modification or surface texturing. This work presents a droplet actuating platform to control the wetting behaviour of water droplets using L-DEP. The exploitation of high electric fields at the droplet solid–liquid interface reduced the operating voltages. The operating voltage can be further reduced, to as low as 30 V, by introducing a lubricant layer to minimise the droplet contact angle hysteresis, thus requiring a smaller L-DEP bulk force. The outcomes of this study will provide a new pathway for developing energy-efficient and reliable droplet actuating platforms to clean a variety of surfaces. A particular interest will be the application of this system in the automobile sector, for instance, to clean headlamps, sensors, cameras, door mirrors, front side glass, and rear screen.